2011
DOI: 10.3390/ijms12053352
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant, Antioxidant and Antitumor Activities of Heterofucans from the Seaweed Dictyopteris delicatula

Abstract: In the present study, six families of sulfated polysaccharides were obtained from seaweed Dictyopteris delicatula by proteolytic digestion, followed by acetone fractionation and molecular sieving on Sephadex G-100. Chemical analyses demonstrated that all polysaccharides contain heterofucans composed mainly of fucose, xylose, glucose, galactose, uronic acid, and sulfate. The fucans F0.5v and F0.7v at 1.0 mg/mL showed high ferric chelating activity (∼45%), whereas fucans F1.3v (0.5 mg/mL) showed considerable red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 35 publications
4
45
1
1
Order By: Relevance
“…In hydroxyl scavenging assay and ferrous chelating, no activity was found, although, this result is similar to the most of sulfated polysaccharides reported in literature that displayed very low activity in these assays (Magalhães et al, 2011). However, sulfated heterofucans from Padina gymnospora (Souza et al, 2007), as well as, sulfated homofucans from Fucus vesiculosus and Laminaria japonica (Souza et al, 2007;Wang et al, 2008), have high activity as hydroxyl radical scavengers.…”
Section: Discussionsupporting
confidence: 56%
“…In hydroxyl scavenging assay and ferrous chelating, no activity was found, although, this result is similar to the most of sulfated polysaccharides reported in literature that displayed very low activity in these assays (Magalhães et al, 2011). However, sulfated heterofucans from Padina gymnospora (Souza et al, 2007), as well as, sulfated homofucans from Fucus vesiculosus and Laminaria japonica (Souza et al, 2007;Wang et al, 2008), have high activity as hydroxyl radical scavengers.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, researchers often use the reducing power as an important standard for evaluating the antioxidant ability [28, 29]. Commonly, the reduction of three-valent iron ion to two-valent iron ion is determined at the absorbance 700 nm, and ascorbic acid is used as control in assay of reduction ability.…”
Section: Resultsmentioning
confidence: 99%
“…Fucans from various seaweeds, including different Dictyotales [3,4], possess anticoagulant activity. In this way, we evaluated the anticoagulant activity of the Fuc C test by Prothrombin time (PT) and Partial thromboplastin time (APTT).…”
Section: Resultsmentioning
confidence: 99%
“…They are a family of homo- and hetero-polysaccharides having in its constitution monomer sulfated l -fucose [3]. Recent studies have demonstrated that fucans presented various pharmacological activities, such as: anticoagulant [4], antioxidant [5], immune modulator [6], anti-viral [7,8], anti-inflammatory [9] and anti-tumoral [10]. …”
Section: Introductionmentioning
confidence: 99%